When someone you know is gay - Cohen, Susan 1938- (M. Evans, 1989)
Describes the history, possible causes, and social, religious, and political aspects of male and female homosexuality, with an emphasis on the problems experienced by gay teens in coming out to family and friends. Includes a list of organizations to contact for help and more information.